Enterprise Surveys : St. Kitts and Nevis Country Profile 2010 - World Bank; International Finance Corporation (Washington, DC, 2014)
The enterprise surveys focus on the many factors that shape the business environment. The country profile for St. Kitts and Nevis is based on data from the enterprise surveys conducted by the World Bank. The qualitative and quantitative data collected through the surveys connect a countryapos;s business environment characteristics with firm productivity and performance. The topics covered include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, finance, innovation, labor, and perceptions about obstacles to doing business. The benchmarks include the averages for the group of countries in Latin America and Caribbean and the St. Kitts and Nevis income group. Breakdowns by firm size are presented in the appendix along with all indicators used to make the graphs.